Incremental value of 68-gallium-prostate-specific membrane antigen positron emission tomography/computed tomography in patients with abnormal prostate-specific antigen and benign transrectal ultrasound biopsy - Gupta, Manoj (Urol Ann, 2018)
INTRODUCTION: Bladder outlet obstruction due to prostate enlargement is a common health problem in male and frequently investigated with prostate-specific antigen (PSA) and transrectal ultrasound (TRUS). TRUS-guided biopsy is critical to differentiate benign prostatic hyperplasia (BPH) or prostate cancer (PCa) even though it has been associated with false negative with reported 3%–16% incidence of PCa in BPH specimens. Prostate-specific membrane antigen positron emission tomography/computed tomography (PSMA PET/CT), a targeted molecular imaging for PCa, has showed promising results in recurrence and staging. We analyzed its role in patients with abnormal PSA and benign TRUS biopsy. MATERIAL AND METHODS: Of 558 (68)Ga-PSMA PET/CT performed from July 2014 to February 2017, we found six patients with abnormal PSA (range 8.2–24.2 ng/ml, median: 13.3 ng/ml) with benign 12 cores TRUS biopsy as indication. These cases were reanalyzed in detail. Spearman's rank test was used entire correlation using SPSS version 21. RESULTS: (68)Ga-PSMA PET/CT showed mild diffuse tracer uptake in prostate in all patients with no focality and maximum standard uptake value normalized to body weight (SUV(max)) range was 3.2-5.8 (median: 3.9). Two patients with PSA <10 ng/ml had normal (68)Ga-PSMA PET/CT and underwent medical management. In other four patients with PSA >10 ng/ml, two showed metastatic disease in pelvic lymph node in both and in lung in one; hence, (68)Ga-PSMA PET/CT changed these patients' management. Spearman's rank test showed no correlation with baseline PSA and SUV(max) of prostate (r(s) −0.0287, P = 0.9571) while strong positive correlation was seen with baseline PSA and (68)Ga-PSMA PET/CT scan positivity for extraprostatic disease (r(s) = 0.828, P = 0.042). CONCLUSIONS: (68)Ga-PSMA whole-body PET/CT can provide useful incremental information in patient with high PSA and negative TRUS biopsy and has a potential to guide management in this subgroup of PCa patients.